A repercussão da organização do processo na sentença - Nunes, Liliane Emerick (2023)
In the present work, the study of the repercussions of the organization of the process in the sentence is carried out. Therefore, the modalities created by the Civil Procedure Code of 2015 are evaluated, in order to guarantee the cooperation of all procedural subjects in the execution of the task. The research is also concerned with studying the expected and authorized form of action by procedural subjects in identifying matters of fact and law relevant to the judgment on the merits, as well as the evidence and its burden. The organization of the process, then, is evaluated as a point of encounter and balance between the freedoms of the parties and the instructive power of the judge and his duties. The study follows with regard to the peculiarities of the stability of the organizational pronouncement and its importance for the sentence. Next, the organization of the process is identified as a condensation of the postulatory phase and an instrument for monitoring respect for the principle of congruence, in order to then relate it to the grounds for the judgment. In view of the indispensability of carrying out the organization of the process and the need to observe its precepts in the sentence, we move on to the study of the procedural instruments available to the parties to contest the sentence that disregards the pronouncement of organization.